Ocular Dominance and Functional Asymmetry in Visual Attention Networks - Liu, Sinan; Zhao, Bingyang; Shi, Chaoqun; Ma, Xuying; Sabel, Bernhard A.; Chen, Xiping; Tao, Luyang (Investigative ophthalmology & visual science, 2021)
The dorsal attention network (DAN) and the ventral attention network (VAN) are known to support visual attention, but the influences of ocular dominance on the attention networks are unclear. We aimed to explore how visual cortical asymmetry of the attention networks correlate with neurophysiological oscillation and connectivity markers of attentional processes. An oddball task with concentric circle stimuli of three different sizes (i.e., spot size of 5°, 20°, or 30° of visual angle) was used to vary task difficulty. Event-related oscillations and interareal communication were tested with an electroencephalogram-based visual evoked components as a function of ocular dominance in 30 healthy subjects. Accuracy rates were higher in the dominant eyes compared with the nondominant eyes. Compared with the nondominant eyes, the dominant eyes had higher theta, low-alpha, and low-beta powers and lower high-alpha powers within the nodes of VAN and DAN. Furthermore, visual information processed by the dominant and nondominant eye had different fates, that is, the dominant eyes mainly relied on theta and low-alpha connectivity within both the VAN and the DAN, whereas the nondominant eyes mainly relied on theta connectivity within the VAN and high-alpha connectivity within the DAN. The difference in accuracy rate between the two eyes was correlated with the low-alpha oscillations in the anterior DAN area and low-alpha connectivity of the left DAN. The ocular dominance processing and interareal communication reveal a cortical asymmetry underlying attention, and this reflects a two-way modulatory mechanism within attention networks in the human brain.